Edukasi Vulva Hygiene Saat Menstruasi Melalui Media Audiovisual Diam Meningkatkan Pengetahuan Remaja Putri - Safitri, Nadiah Eka Ayu; Murtiningsih, Dewi; Handajani, Sih Rini (Jurnal Empathy Pengabdian Kepada Masyarakat, 2023)
Background: Low knowledge about vulva hygiene during menstruation among adolescent girls is a major problem that can contribute to the risk of reproductive organ infections. This community service programme aims to increase adolescent girls' knowledge about vulva hygiene during menstruation through education using silent audiovisual media. Methods: The activity was conducted in the Olehsari Village Office Hall on 4–5 June 2022, involving 76 adolescent girls aged 10–21 years as partners, selected using purposive sampling. Socialisation, counselling, and evaluation were carried out using a pretest-posttest method with a knowledge questionnaire, supported by question and answer sessions and direct explanations from the community service team.  Results: The evaluation of the results showed a significant increase in the average knowledge of the participants from a score of 62.43 (pretest) to 82.57 (posttest), as indicated by an average increase in knowledge scores of 20.14 points (p = <0.001; Wilcoxon test). Conclusion: Edukasi melalui audiovisual mampu meningkatkan soft skill dan hardskill peserta dalam hal pemahaman dan praktik vulva hygiene saat menstruasi secara bermakna. Program ini direkomendasikan sebagai model edukasi kesehatan remaja putri berbasis media audiovisual pada komunitas desa.